Internalization of Noble Values in Consumer Behavior (A Study on the Phenomenon of Online Shopping among Millennials) - Angelika Pratiwi Widya Nugroho; Selamet Riyadi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Internalization of moral values is a control mechanism for balancing consumer behavior. This study aims to analyze how moral values can be internalized in the consumer behavior of the millennial generation, particularly in the online shopping phenomenon. The development of sophisticated technology, the availability of online ordering for all needs, and the ease of transactions have given rise to new consumption patterns that often lead to excessive consumer behavior. Moral values, which include honesty, simplicity, responsibility, and local wisdom, can serve as a moral control mechanism in addressing consumer culture. This study used a qualitative approach with literature review and observation of millennial online shopping behavior. The results show that internalization of moral values can foster wise consumption behavior, prioritizing needs over wants, and maintaining a balance between material satisfaction and spiritual values. The implications of this research are the importance of culturally based values education and digital literacy in efforts to shape a healthy consumer generation of millennials.